Protecting dogs against attacks by wolves (Canis lupus), with comparison to African wild dogs (Lycaon pictus) and dholes (Cuon alpinus) - Fedderwitz, Frauke (Institutionen för fysik, kemi och biologi, 2010)
In this thesis five different protection harnesses for hunting dogs against canidae attacks were assessed. Hunting dogs can be attacked and severely injured or killed by wolves (Canis lupus) when released during hunting. So far there is no effective protection method. Similar problems are reported with African wild dogs (Lycaon pictus) and dholes (Cuon alpinus) with other domestic animals. In this study the experimental harnesses were presented on a dummy to lure the animals to attack them. The harnesses with physical (screws or spikes on the back) and ultrasound (immediate bite controlled and 19 second continuous ultrasound) deterrents were only assessed during wolf attacks, whereas the harness with electric shocks was also tested on the other two species. Neither physical nor ultrasound deterrents showed a large enough aversive response in the wolves. Electric shocks, given to the animals when biting the dummy, triggered an immediate release of the dummy in all three species. Long term effects differed between species and individuals. The exposed wolf did not touch the dummy again after a second exposure, whereas all except one African wild dog bit the dummy again in consecutive trials. Some individuals returned to bite a second time even in the same trial. An assessment of the long term effect on dholes was not possible, as the individuals were undistinguishable. Based on the data obtained in this study a harness with electric deterrent seems the most promising.